Main and fine grid integrated HJT silver paste and preparation method thereof

By developing the integrated HJT silver paste of main and fine grids, the problem of printing in HJT photovoltaic cells is solved in two steps, efficient preparation and low-cost production are achieved, and the conductivity and yield of the product are improved.

CN119541923APending Publication Date: 2025-02-28SUZHOU BETELY POLYMER MATERIALS CO LTD

Patent Information

Application Number
CN202411789256.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

During the production process, the main fine grid printing of HJT photovoltaic cells is divided into two steps, which increases the production link and cost, affecting the product yield rate.

Method used

A master-fine gate integrated HJT silver paste is developed to achieve efficient preparation of silver paste by optimizing the particle size distribution of silver powder and the composition of resin, combined with appropriate curing agents and catalysts.

Benefits of technology

The high welding tension and adhesion of silver paste is achieved, which reduces the intrinsic resistance of the paste, improves conductivity, simplifies the production process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005174917810000091
    Figure BDA0005174917810000091
  • Figure BDA0005174917810000101
    Figure BDA0005174917810000101
  • Figure HDA0005174917820000011
    Figure HDA0005174917820000011
Patent Text Reader

Abstract

The main and fine grid integrated HJT silver paste comprises the following components in percentage by mass: 85-92% of silver powder, 2-6% of organic resin, 0.5-2% of a curing agent, 0-1% of a thixotropic agent, 0-1% of an epoxy catalyst, a silicone oil catalyst and 2-5% of an organic solvent. The silver powder at least comprises three kinds of powder with different particle sizes, wherein the ball powder and the ball-like powder with the D50 being 2-6 micrometers and the tap density being 5-6 g / mL account for 30%-50% in one kind, the ball powder and the ball-like powder with the D50 being 0.1-1 micrometer and the tap density being 3-5 g / mL account for 20%-40% in the second kind, and the sheet powder with the D50 being 0.5-2 micrometers and the tap density being 3-5 g / mL account for 10%-30% in the third kind.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a conductive silver paste and a preparation technology thereof, and specifically to a main-fine-grid integrated HJT silver paste and a preparation method thereof. Background Art

[0002] With the development of new energy vehicles, the demand for electricity has increased year by year. Traditional thermal power generation has the disadvantage of high carbon emissions and is gradually becoming unpopular. Although hydropower and nuclear power are environmentally friendly, they have high investment costs and slow development.

[0003] As a sustainable new energy source, solar photovoltaics are gaining increasing attention for their simple installation and low cost. In recent years, solar cell technology has evolved rapidly, with TOPCON cells becoming the current mainstream. HJT photovoltaic cells, also known as heterojunction cells, are a relatively recent development. By passivating the front and back surfaces of the crystalline silicon substrate, HJT cells effectively prevent the recombination of photogenerated carriers and increase their lifetime, thereby improving conversion efficiency. Combining the advantages of crystalline silicon cells and thin-film cells, these cells offer improved conversion efficiency and are expected to replace TOPCON cells.

[0004] While HJT photovoltaic cells offer excellent conversion rates, their high cost has slowed their development. Multiple printing processes are a significant factor impacting HJT photovoltaic cell costs. As is well known, HJT silver paste printing involves printing both main and fine grids, making simultaneous main and fine grid printing impossible. This increases production steps, impacts product yield, and leads to higher cell costs. Integrated main and fine grids are a key technology that can address the complexity of paste printing and reduce both printing and production costs.

[0005] Therefore, it is necessary to provide a main and fine gate integrated HJT silver paste and a preparation method thereof to solve the above problems. Summary of the Invention

[0006] The object of the present invention is to provide a main-fine-grid integrated HJT silver paste and a preparation method thereof.

[0007] One of the technical solutions is as follows:

[0008] A main-fine grid integrated HJT silver paste, comprising the following components, by mass percentage: 85-92% silver powder, 2-6% organic resin, 0.5-2% curing agent, 0-1% thixotropic agent, 0-1% epoxy catalyst, silicone oil catalyst, and 2-5% organic solvent;

[0009] Silver powder includes ball powder, ball-like powder and flake powder:

[0010] Silver powder contains at least three types of powders with different particle sizes, one of which is spherical powder and spherical-like powder with a D50 of 2 to 6 μm and a tap density of 5-6 g / mL, accounting for 30% to 50%; the second type is spherical powder and spherical-like powder with a D50 of 0.1 to 1 μm and a tap density of 3-5 g / mL, accounting for 20-40%; and the third type is flake powder with a D50 of 0.5 to 2 μm and a tap density of 3-5 g / mL, accounting for 10-30%.

[0011] Furthermore, the resin is composed of a main resin and an auxiliary resin, and the main resin is two or more of phenoxy resin JER1007, 1010, 1004, PKHB, PKHH, epoxy resin 4007P, 4010P, 7787, 3150, 2021P, polyester resin Vylon-GK888, BX-7000A, 270, ES410, ES420, polyurethane resin TPU5778, TPU 5703, TPU58887;

[0012] The auxiliary resin is a modified resin, which is pre-synthesized by using a modifier. The modifier includes a silane coupling agent, a titanate coupling agent, and a polyetheramine. The silane coupling agents include KH550, KH560, P-S496, and SCA-A20F; the titanate coupling agents include TCA-KTTS, TCA-238J, TCA-K55, TCA-K44, and TCA-KTTT; the phosphate polyetheramines include Baxxodur EC301, EC302, D230, and D400; the resins include epoxy resins jER 827, 806, TT386, and GE60; and the polyester polyols Dynacoll 7110, 7111, 7360, and 7380. The resin is a low molecular weight liquid resin containing at least two functional groups.

[0013] Furthermore, in the auxiliary resin synthesis, the ratio of the modifier to the resin is 1 to 5:100. The resin to be modified is added to the reactor, and the modifier is gradually added. The mixture is heated to 70 to 95° C. and stirred for 1 to 2 hours until the resin forms a homogeneous phase without any reaction. The mixture is allowed to stand and cool to room temperature, and filtered with a 300 to 400 mesh cloth to obtain a liquid modified resin.

[0014] The thixotropic agents used include dimethyl silicone oil, vinyl silicone oil, methoxy silicone oil, ethoxy silicone oil, polyether silicone oil, and hydroxy silicone oil;

[0015] The epoxy curing agent used is two or more of a variety of blocked isocyanate curing agents, with an unblocking temperature of 80 to 150°C, preferably a curing temperature of 90 to 130°C;

[0016] The epoxy catalyst used is an imidazole diacid composite catalyst. The molar ratio of imidazole to diacid is 1:1. N-methylpyrrolidone is added to the reactor, and imidazole and diacid are added gradually and sequentially. The mixture is stirred at room temperature until it is homogeneous and there is no reaction. The mixture is allowed to cool to room temperature to obtain a composite catalyst.

[0017] Furthermore, the imidazole is benzimidazole, DBU, dimethyltetraethylimidazole, PN23, PN23J, PN40, and the diacid is an organic acid diacid adipic acid, succinic acid, glutaric acid, or sebacic acid;

[0018] The silicone oil catalyst is Custer catalyst, tetramethylammonium chloride, or Custer silicone oil type platinum catalyst.

[0019] Furthermore, the organic solvent is one or more of propylene carbonate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol butyl ether acetate, dimethyl adipate, diethyl adipate, propylene glycol methyl ether acetate, and terpineol.

[0020] Technical solution 2:

[0021] A main-fine gate integrated HJT silver paste and a preparation method thereof, comprising the following steps:

[0022] 1) Add 2-5% organic solvent into a reaction kettle and mix, then add 2-5% resin, heat and stir, cool to room temperature, filter, and obtain a resin solution. The heating temperature is 70-95°C and the stirring speed is 200-300 r / min for 1-2 hours.

[0023] 2) adding 0.01-1% of a catalyst, 0.01-1% of a thixotropic agent, 0.5-2% of a curing agent, and 1-2% of a diluent to the resin solution prepared in step 1) in sequence, and centrifuging and dispersing the mixture to obtain an organic carrier at a centrifugal dispersion speed of 800-850 rpm for 2-4 minutes;

[0024] 3) adding 87-93% of silver powder to the organic vehicle prepared in step 2), centrifugally dispersing the mixture, shearing the mixture on a three-roll mill until the slurry fineness is less than 5 μm, and filtering the mixture to obtain a finished silver paste. The specific process of centrifugal dispersion is as follows: dispersing the mixture at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1-3 min each.

[0025] Compared with the existing technology, the present invention has the properties of good meshing performance of fine grid, low volume resistivity, excellent contact resistance, etc., and has the high welding tension and adhesion of the main grid; the silver powder is combined with multiple powders, which increases the effective contact points of the silver powder, reduces the intrinsic resistance of the slurry, and maintains a high silver content to ensure that the slurry has good conductivity. The carrier must be compatible with printability and adhesion. Excessive introduction of macromolecular resins will inevitably affect printability. Therefore, more consideration is given to liquid low-molecular resins. However, due to the weak curing ability of the latter, modification is required on this basis. Therefore, additives or curing agents with strong adhesion are introduced into the carrier structure, and these additives react with the resin to produce a large number of hydroxyl groups. These hydroxyl groups ensure the improvement of the curing speed. At the same time, a catalyst and curing agent combination is used in the curing agent, and the catalyst introduces an imidazole diacid structure. This reaction structure ensures the latency of imidazole and the storage time. Moreover, both imidazole and diacid participate in epoxy curing and catalytic reactions, which enhances the resin curing speed and cross-linking degree, continuously improves the adhesion of the resin on the substrate, and multiple guarantees that the silver paste can have a higher welding tensile force on the substrate; the introduction of silicone oil catalyst not only ensures that silicone oil can increase the printing effect of the paste and improve its resistance value, but also reduces the negative effects of silicone oil on the paste. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is one of the effect diagrams of the present invention applied to a battery cell.

[0027] Figure 2 This is the second effect diagram of the present invention applied to a battery cell. DETAILED DESCRIPTION

[0028] Example 1

[0029] A main-fine grid integrated HJT silver paste comprises the following components in percentage by mass: 85% silver powder, 10% resin, 2% curing agent, and 3% organic solvent.

[0030] Among them, silver powder is composed of slurry with D50 of 4μm and tap density of 5g / mL, accounting for 45%; the second type is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL, accounting for 35%; the third type is flake powder with D50 of 1μm and tap density of 3g / mL, accounting for 5%.

[0031] Epoxy resin is the main resin: 6% phenoxy resin PKHH and 4% polyester resin 270.

[0032] Curing agent: It includes isocyanate curing agent and auxiliary curing agent, specifically 1% XB-G282 isocyanate curing agent, the unblocking temperature is 80°C, and 2% SBN-70D isocyanate curing agent, the unblocking temperature is 120°C.

[0033] Organic solvent: 3% diethylene glycol butyl ether acetate.

[0034] The preparation method comprises the following steps:

[0035] (1) 3% diethylene glycol butyl ether acetate organic solvent was mixed in a reaction kettle, 10% resin was gradually added, heated to 85°C, stirred at a speed of 260 r / min for 1 hour until the resin was completely dissolved, allowed to stand, cooled to room temperature, and filtered through a 300-400 mesh cloth to obtain a resin solution;

[0036] (2) taking the prepared resin solution, gradually adding 1% XB-G282 isocyanate curing agent and 2% SBN-70D isocyanate curing agent, dispersing by centrifugation at 800 rpm for 2 minutes, and mixing thoroughly to obtain an organic vehicle;

[0037] (3) Take the prepared organic carrier, add 35% D50 0.5 μm spherical powder and stir, then centrifuge and disperse at speeds of 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively.

[0038] (4) Slowly add the remaining silver powder and stir it manually. After all the silver powder is evenly mixed, centrifuge at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively. After centrifugation, use a three-roller machine to shear and disperse the slurry until the slurry fineness reaches less than 2 μm, and then stop the three rollers.

[0039] (5) Use a 500-mesh sieve to filter out impurities and uneven large particles in the slurry to obtain a main-fine grid integrated HJT silver paste.

[0040] Example 2

[0041] A main-fine grid integrated HJT silver paste comprises the following components by mass percentage: 92% silver powder, 3% resin, 1.5% curing agent, 0.5% vinyl silicone oil, and 3% organic solvent.

[0042] Among them, silver powder is composed of slurry with D50 of 4μm and tap density of 5g / mL, accounting for 42%; the second type is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL, accounting for 40%; the third type is flake powder with D50 of 1μm and tap density of 3g / mL, accounting for 10%.

[0043] Epoxy resin is the main resin: 2% phenoxy resin PKHH and 1% polyester resin 270.

[0044] Curing agent: It includes isocyanate curing agent and auxiliary curing agent, specifically 0.5% XB-G282 isocyanate curing agent, the unblocking temperature is 80℃, 1% SBN-70D isocyanate curing agent, the unblocking temperature is 120℃,

[0045] Thixotropic agent: 0.5% vinyl silicone oil.

[0046] Organic solvent: 3% diethylene glycol butyl ether acetate.

[0047] The preparation method comprises the following steps:

[0048] (1) 3% of diethylene glycol butyl ether acetate organic solvent was mixed in a reaction kettle, and 3% of resin was gradually added, heated to 85°C, and stirred at a speed of 260 r / min for 1 hour until the resin was completely dissolved. The mixture was allowed to stand, cooled to room temperature, and filtered through a 300-400 mesh cloth to obtain a resin solution;

[0049] (2) taking the prepared resin solution, gradually adding 0.5% XB-G282 isocyanate curing agent and 1% SBN-70D isocyanate curing agent, dispersing by centrifugation at 800 rpm for 2 minutes, and mixing thoroughly to obtain an organic vehicle;

[0050] (3) Take the prepared organic carrier, add 40% D50 0.5 μm spherical powder and stir, then centrifuge and disperse at speeds of 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively.

[0051] (4) Slowly add the remaining silver powder and stir it manually. After all the silver powder is evenly mixed, centrifuge at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively. After centrifugation, use a three-roller machine to shear and disperse the slurry until the slurry fineness reaches less than 2 μm, and then stop the three rollers.

[0052] (5) Use a 500-mesh sieve to filter out impurities and uneven large particles in the slurry to obtain a main-fine grid integrated HJT silver paste.

[0053] Comparative Example 1

[0054] A main-fine grid integrated HJT silver paste comprises the following components by mass percentage: 92% silver powder, 2% epoxy resin, 1% auxiliary resin, 1.5% curing agent, 0.5% thixotropic agent, and 3% organic solvent.

[0055] Among them, silver powder is composed of slurry with D50 of 4μm and tap density of 5g / mL, accounting for 47%; the second type is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL, accounting for 40%; the third type is flake powder with D50 of 1μm and tap density of 3g / mL, accounting for 5%.

[0056] Epoxy resin as the main resin: 1% phenoxy resin PKHH and 1% polyester resin 270.

[0057] Auxiliary resin: 1% D400 and jER 827 synthetic resin, the ratio is 1:50, jER 827 is added to the reactor first, and D400 is slowly added dropwise to the reactor. The temperature is heated to 70℃ and the reaction is carried out for 2 hours. If there is no reaction, it is cooled to room temperature for use.

[0058] Curing agent: It includes isocyanate curing agent and auxiliary curing agent, specifically 0.5% XB-G282 isocyanate curing agent, the unblocking temperature is 80℃, 1% SBN-70D isocyanate curing agent, the unblocking temperature is 120℃,

[0059] Thixotropic agent: 0.5% vinyl silicone oil.

[0060] Organic solvent: 3% diethylene glycol butyl ether acetate.

[0061] The preparation method comprises the following steps:

[0062] (1) 3% of diethylene glycol butyl ether acetate organic solvent was mixed in a reaction kettle, and 3% of resin was gradually added, heated to 85°C, and stirred at a speed of 260 r / min for 1 hour until the resin was completely dissolved. The mixture was allowed to stand, cooled to room temperature, and filtered through a 300-400 mesh cloth to obtain a resin solution;

[0063] (2) taking the prepared resin solution, gradually adding 0.5% XB-G282 isocyanate curing agent and 1% SBN-70D isocyanate curing agent, dispersing by centrifugation at 800 rpm for 2 minutes, and mixing thoroughly to obtain an organic vehicle;

[0064] (3) Take the prepared organic carrier, add 10% D50 0.6 μm spherical powder and stir, then centrifuge and disperse at speeds of 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively.

[0065] (4) Slowly add the remaining silver powder and stir it manually. After all the silver powder is evenly mixed, centrifuge at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively. After centrifugation, use a three-roller machine to shear and disperse the slurry until the slurry fineness reaches less than 2 μm, and then stop the three rollers.

[0066] (5) Use a 500-mesh sieve to filter out impurities and uneven large particles in the slurry to obtain a main-fine grid integrated HJT silver paste.

[0067] Comparative Example 2

[0068] A main-fine grid integrated HJT silver paste comprises the following components by mass percentage: 92% silver powder, 2% epoxy resin, 1% auxiliary resin, 1.5% curing agent, 0.5% thixotropic agent, and 3% organic solvent.

[0069] Among them, silver powder is composed of slurry with D50 of 4μm and tap density of 5g / mL, accounting for 47%; the second type is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL, accounting for 40%; the third type is flake powder with D50 of 1μm and tap density of 3g / mL, accounting for 5%.

[0070] Epoxy resin is the main resin: 2% phenoxy resin PKHH and 1% polyester resin 270.

[0071] Auxiliary resin: 1% KH550 and jER 827 synthetic resin, the ratio is 1:50, jER 827 is added to the reactor first, and KH550 is slowly added dropwise to the reactor. The temperature is heated to 70℃ and the reaction is carried out for 2 hours. If there is no reaction, it is cooled to room temperature for use.

[0072] Curing agent: It includes isocyanate curing agent and auxiliary curing agent, specifically 0.5% XB-G282 isocyanate curing agent, the unblocking temperature is 80℃, 1% SBN-70D isocyanate curing agent, the unblocking temperature is 120℃,

[0073] Thixotropic agent: 0.5% vinyl silicone oil.

[0074] Organic solvent: 3% diethylene glycol butyl ether acetate.

[0075] The preparation method comprises the following steps:

[0076] (1) 3% of diethylene glycol butyl ether acetate organic solvent was mixed in a reaction kettle, and 3% of resin was gradually added, heated to 85°C, and stirred at a speed of 260 r / min for 1 hour until the resin was completely dissolved. The mixture was allowed to stand, cooled to room temperature, and filtered through a 300-400 mesh cloth to obtain a resin solution;

[0077] (2) taking the prepared resin solution, gradually adding 0.5% XB-G282 isocyanate curing agent and 1% SBN-70D isocyanate curing agent, dispersing by centrifugation at 800 rpm for 2 minutes, and mixing thoroughly to obtain an organic vehicle;

[0078] (3) Take the prepared organic carrier, add 10% D50 0.6 μm spherical powder and stir, then centrifuge and disperse at speeds of 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively.

[0079] (4) Slowly add the remaining silver powder and stir it manually. After all the silver powder is evenly mixed, centrifuge at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively. After centrifugation, use a three-roller machine to shear and disperse the slurry until the slurry fineness reaches less than 2 μm, and then stop the three rollers.

[0080] (5) Use a 500-mesh sieve to filter out impurities and uneven large particles in the slurry to obtain a main-fine grid integrated HJT silver paste.

[0081] Comparative Example 3

[0082] A main-fine grid integrated HJT silver paste comprises the following components by mass percentage: 92% silver powder, 2% epoxy resin, 1% auxiliary resin, 1.5% curing agent, 0.5% thixotropic agent, and 3% organic solvent.

[0083] Among them, silver powder is composed of slurry with D50 of 4μm and tap density of 5g / mL, accounting for 47%; the second type is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL, accounting for 40%; the third type is flake powder with D50 of 1μm and tap density of 3g / mL, accounting for 5%.

[0084] Epoxy resin as the main resin: 1% phenoxy resin PKHH and 1% polyester resin 270.

[0085] Auxiliary resin: Add 1% (0.5%) D400 and jER 827 synthetic resin in a ratio of 1:50. Add jER 827 to the reactor first, then slowly add D400 dropwise. Heat to 70°C and react for 2 hours. If no reaction occurs, cool to room temperature before use. Add 0.5% KH550 and jER 827 synthetic resin in a ratio of 1:50. Add jER 827 to the reactor first, then slowly add KH550 dropwise. Heat to 70°C and react for 2 hours. If no reaction occurs, cool to room temperature before use.

[0086] Curing agent: It includes isocyanate curing agent and auxiliary curing agent, specifically 0.5% XB-G282 isocyanate curing agent, the unblocking temperature is 80℃, 1% SBN-70D isocyanate curing agent, the unblocking temperature is 120℃,

[0087] Thixotropic agent: 0.5% vinyl silicone oil.

[0088] Organic solvent: 3% diethylene glycol butyl ether acetate.

[0089] The preparation method comprises the following steps:

[0090] (1) 3% of diethylene glycol butyl ether acetate organic solvent was mixed in a reaction kettle, and 3% of resin was gradually added, heated to 85°C, and stirred at a speed of 260 r / min for 1 hour until the resin was completely dissolved. The mixture was allowed to stand, cooled to room temperature, and filtered through a 300-400 mesh cloth to obtain a resin solution;

[0091] (2) taking the prepared resin solution, gradually adding 0.5% XB-G282 isocyanate curing agent and 1% SBN-70D isocyanate curing agent, dispersing by centrifugation at 800 rpm for 2 minutes, and mixing thoroughly to obtain an organic vehicle;

[0092] (3) Take the prepared organic carrier, add 10% D50 0.6 μm spherical powder and stir, then centrifuge and disperse at speeds of 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively.

[0093] (4) Slowly add the remaining silver powder and stir it manually. After all the silver powder is evenly mixed, centrifuge at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively. After centrifugation, use a three-roller machine to shear and disperse the slurry until the slurry fineness reaches less than 2 μm, and then stop the three rollers.

[0094] (5) Use a 500-mesh sieve to filter out impurities and uneven large particles in the slurry to obtain a main-fine grid integrated HJT silver paste.

[0095] Comparative Example 4

[0096] A main-fine grid integrated HJT silver paste comprises the following components by mass percentage: 92% silver powder, 2% epoxy resin, 1% auxiliary resin, 1.5% curing agent, 0.5% thixotropic agent, and 3% organic solvent.

[0097] Among them, silver powder is composed of slurry with D50 of 4μm and tap density of 5g / mL, accounting for 47%; the second type is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL, accounting for 40%; the third type is flake powder with D50 of 1μm and tap density of 3g / mL, accounting for 5%.

[0098] Epoxy resin as the main resin: 1% phenoxy resin PKHH and 1% polyester resin 270.

[0099] Auxiliary resin: Add 1% (0.5%) D400 and jER 827 synthetic resin in a ratio of 1:50. Add jER 827 to the reactor first, then slowly add D400 dropwise. Heat to 70°C and react for 2 hours. If no reaction occurs, cool to room temperature before use. Add 0.5% KH550 and jER 827 synthetic resin in a ratio of 1:50. Add jER 827 to the reactor first, then slowly add KH550 dropwise. Heat to 70°C and react for 2 hours. If no reaction occurs, cool to room temperature before use.

[0100] Curing agent: It includes isocyanate curing agent and auxiliary curing agent, specifically 0.5% XB-G282 isocyanate curing agent, the unblocking temperature is 80°C, and 1% SBN-70D isocyanate curing agent, the unblocking temperature is 120°C.

[0101] Thixotropic agent: 0.5% vinyl silicone oil.

[0102] Synthetic catalyst: 0.1% dimethyltetraethylimidazole and succinic acid complex

[0103] Organic solvent: 3% diethylene glycol butyl ether acetate.

[0104] The preparation method comprises the following steps:

[0105] (1) 3% of diethylene glycol butyl ether acetate organic solvent was mixed in a reaction kettle, and 3% of resin was gradually added, heated to 85°C, and stirred at a speed of 260 r / min for 1 hour until the resin was completely dissolved. The mixture was allowed to stand, cooled to room temperature, and filtered through a 300-400 mesh cloth to obtain a resin solution;

[0106] (2) taking the prepared resin solution, gradually adding 0.5% XB-G282 isocyanate curing agent and 1% SBN-70D isocyanate curing agent, dispersing by centrifugation at 800 rpm for 2 minutes, and mixing thoroughly to obtain an organic vehicle;

[0107] (3) Take the prepared organic carrier, add 10% D50 0.6 μm spherical powder and stir, then centrifuge and disperse at speeds of 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively.

[0108] (4) Slowly add the remaining silver powder and stir it manually. After all the silver powder is evenly mixed, centrifuge at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively. After centrifugation, use a three-roller machine to shear and disperse the slurry until the slurry fineness reaches less than 2 μm, and then stop the three rollers.

[0109] (5) Use a 500-mesh sieve to filter out impurities and uneven large particles in the slurry to obtain a main-fine grid integrated HJT silver paste.

[0110] Comparative Example 5

[0111] A main-fine grid integrated HJT silver paste comprises the following components by mass percentage: 92% silver powder, 2% epoxy resin, 1% auxiliary resin, 1.5% curing agent, 0.5% thixotropic agent, and 3% organic solvent.

[0112] Among them, silver powder is composed of slurry with D50 of 4μm and tap density of 5g / mL, accounting for 47%; the second type is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL, accounting for 40%; the third type is flake powder with D50 of 1μm and tap density of 3g / mL, accounting for 5%.

[0113] Epoxy resin as the main resin: 1% phenoxy resin PKHH and 1% polyester resin 270.

[0114] Auxiliary resin: Add 1% (0.5%) D400 and jER 827 synthetic resin in a ratio of 1:50. Add jER 827 to the reactor first, then slowly add D400 dropwise. Heat to 70°C and react for 2 hours. If no reaction occurs, cool to room temperature before use. Add 0.5% KH550 and jER 827 synthetic resin in a ratio of 1:50. Add jER 827 to the reactor first, then slowly add KH550 dropwise. Heat to 70°C and react for 2 hours. If no reaction occurs, cool to room temperature before use.

[0115] Curing agent: It includes isocyanate curing agent and auxiliary curing agent, specifically 0.5% XB-G282 isocyanate curing agent, the unblocking temperature is 80°C, and 1% SBN-70D isocyanate curing agent, the unblocking temperature is 120°C.

[0116] Thixotropic agent: 0.5% vinyl silicone oil.

[0117] Synthetic catalyst: 0.1% dimethyltetraethylimidazole and succinic acid complex

[0118] Silicone oil catalyst: platinum catalyst

[0119] Organic solvent: 3% diethylene glycol butyl ether acetate.

[0120] The preparation method comprises the following steps:

[0121] (1) 3% of diethylene glycol butyl ether acetate organic solvent was mixed in a reaction kettle, and 3% of resin was gradually added, heated to 85°C, and stirred at a speed of 260 r / min for 1 hour until the resin was completely dissolved. The mixture was allowed to stand, cooled to room temperature, and filtered through a 300-400 mesh cloth to obtain a resin solution;

[0122] (2) taking the prepared resin solution, gradually adding 0.5% XB-G282 isocyanate curing agent and 1% SBN-70D isocyanate curing agent, dispersing by centrifugation at 800 rpm for 2 minutes, and mixing thoroughly to obtain an organic vehicle;

[0123] (3) Take the prepared organic carrier, add 10% D50 0.6 μm spherical powder and stir, then centrifuge and disperse at speeds of 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively.

[0124] (4) Slowly add the remaining silver powder and stir it manually. After all the silver powder is evenly mixed, centrifuge at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 minute respectively. After centrifugation, use a three-roller machine to shear and disperse the slurry until the slurry fineness reaches less than 2 μm, and then stop the three rollers.

[0125] (5) Use a 500-mesh sieve to filter out impurities and uneven large particles in the slurry to obtain a main-fine grid integrated HJT silver paste.

[0126] Table 1 shows the substances included in the examples and comparative examples.

[0127]

[0128]

[0129] Among them, A1 is ball powder and spherical powder with D50 of 4μm and tap density of 5g / mL; A2 is ball powder and spherical powder with D50 of 0.5μm and tap density of 4.5g / mL; A3 is flake powder with D50 of 1μm and tap density of 3g / mL; modified resin 1 is D400 and jER827 synthetic resin; modified resin 2 is KH550 and jER 827 synthetic resin.

[0130] As can be seen from the above table, compared with Example 1, Example 2 increases the addition of flake powder, which improves the slurry resistivity, but has a negative impact on the amount of ink applied.

[0131] Compared with Example 2, Comparative Example 1 reduces the amount of flake powder added and increases the auxiliary resin. By reducing the amount of flake powder added, the resistivity of the slurry decreases, the ink volume increases, and the overall resistance of the slurry decreases; by increasing the auxiliary resin, the welding tensile force of the slurry increases.

[0132] Compared with Comparative Example 1, the auxiliary resin was replaced in Comparative Example 2. The welding tensile force of the slurry remained unchanged, but the resistance value decreased, indicating that the type of auxiliary resin also affects the resistance value. Because D400 polyetheramine resin participates in the synthesis of the auxiliary resin, D400 has good flexibility, but its heat resistance and adhesion are inferior to those of the coupling agent KH550, and the welding tensile force decreases slightly.

[0133] Compared to Comparative Examples 1 and 2, Comparative Example 3 added two auxiliary resins, each with a 1:1 resin ratio, which improved both the slurry resistance and weld strength. Comparative Examples 4 and 5, compared to Comparative Example 3, added a synthetic catalyst and a silicone oil catalyst, respectively. Adding the synthetic catalyst to the slurry further increased the weld strength, likely because the catalyst contains dual curing agents: imidazole and diacid. The imidazole helps further cure the slurry, while the diacid also participates in the curing of the epoxy resin and accelerates the curing speed of the epoxy resin. This synthetic catalyst can enhance resin curing and adhesion. Adding a silicone oil catalyst can help the silicone oil in the slurry cure. The addition of silicone oil can help the slurry adhere to the screen, reduce resistance, and increase ink delivery, but may affect slurry adhesion and overlap resistance. Adding this silicone oil catalyst can help the silicone oil in the slurry cure, reducing the impact on overlap resistance and slightly improving weld strength.

[0134] The effect diagram of the present invention applied to the battery cell can be found in Figure 1 、 2 .

[0135] Compared with the existing technology, the present invention has the properties of good meshing performance of fine grid, low volume resistivity, excellent contact resistance, etc., and has the high welding tension and adhesion of the main grid;

[0136] The silver powder is combined with multiple powders to increase the effective contact points of the silver powder, reduce the intrinsic resistance of the paste, and maintain a high silver content to ensure good conductivity. The carrier must be compatible with both printability and adhesion. The introduction of excessive macromolecular resins will inevitably affect printability. Therefore, more consideration is given to liquid low-molecular resins. However, due to the latter's weak curing ability, modification is required. Therefore, a strong adhesion additive or curing agent is introduced into the carrier structure. These additives react with the resin to produce a large number of hydroxyl groups, which ensures improved curing speed. At the same time, a catalyst is used in combination with the curing agent. The catalyst introduces an imidazole diacid structure. This reaction structure ensures the imidazole latency and storage time. Both imidazole and diacid participate in the epoxy curing and catalytic reaction, enhancing the resin curing speed and crosslinking degree, continuously improving the resin adhesion to the substrate, and multiple ways to ensure that the silver paste can have high soldering tensile strength on the substrate. The introduction of silicone oil catalyst ensures that the silicone oil can enhance the printing effect of the paste and improve its resistance value while reducing the negative effects of silicone oil on the paste.

[0137] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the inventive concept of the present invention, which all fall within the scope of protection of the present invention.

Claims

1. A main and fine gate integrated HJT silver paste, characterized by: The composition comprises the following components by mass percentage: 85-92% silver powder, 2-6% organic resin, 0.5-2% curing agent, 0-1% thixotropic agent, 0-1% epoxy catalyst, silicone oil catalyst, and 2-5% organic solvent; Silver powder includes ball powder, spherical powder and flake powder: Silver powder contains at least three kinds of powders with different particle sizes, one of which is ball powder and ball-like powder with D50 of 2-6μm and tap density of 5-6g / mL, accounting for 30%-50%, the second is ball powder and ball-like powder with D50 of 0.1-1μm and tap density of 3-5g / mL, accounting for 20-40%, and the third is flake powder with D50 of 0.5-2μm and tap density of 3-5g / mL, accounting for 10-30%.

2. The main and fine gate integrated HJT silver paste according to claim 1, characterized in that: The resin is composed of a main resin and an auxiliary resin. The main resin is two or more of phenoxy resin JER1007, 1010, 1004, PKHB, PKHH, epoxy resin 4007P, 4010P, 7787, 3150, 2021P, polyester resin Vylon-GK888, BX-7000A, 270, ES410, ES420, polyurethane resin TPU5778, TPU 5703, TPU58887.

3. The main-fine gate integrated HJT silver paste according to claim 2, characterized in that: The auxiliary resin is a modified resin, which is pre-synthesized by using a modifier. The modifier includes a silane coupling agent, a titanate coupling agent, and a polyetheramine. The silane coupling agent is KH550, KH560, P-S496, and SCA-A20F. The titanate coupling agent is TCA-KTTS, TCA-238J, TCA-K55, TCA-K44, and TCA-KTTT. The phosphoric acid polyetheramine is Baxxodur EC301, EC302, D230, and D400. The resin includes epoxy resins JER827, 806, TT386, and GE60. The polyester polyols are Dynacoll 7110, 7111, 7360, and 7380. The resin is a low molecular weight liquid resin and contains at least two functional groups. In the auxiliary resin synthesis, the ratio of modifier to resin is 1 to 5:

100. The resin to be modified is added into the reaction kettle, and the modifier is gradually added. The mixture is heated to 70 to 95°C and stirred for 1 to 2 hours until the resin forms a homogeneous phase without any reaction. The mixture is allowed to stand and cool to room temperature, and filtered with a 300 to 400 mesh cloth to obtain a liquid modified resin.

4. The main-fine gate integrated HJT silver paste according to claim 3, characterized in that: The thixotropic agent used includes dimethyl silicone oil, vinyl silicone oil, methoxy silicone oil, ethoxy silicone oil, polyether silicone oil, and hydroxy silicone oil.

5. The main and fine gate integrated HJT silver paste according to claim 4, characterized in that: The epoxy curing agent used is two or more of a plurality of blocked isocyanate curing agents, and the unblocking temperature is 80 to 150° C., preferably a curing temperature of 90 to 130° C.

6. The main and fine gate integrated HJT silver paste according to claim 1, characterized in that: The epoxy catalyst used is an imidazole diacid composite catalyst, the molar ratio of imidazole to diacid is 1:1, N-methylpyrrolidone is added into the reaction kettle, imidazole and diacid are added gradually and sequentially, stirred at room temperature until homogeneous, without any reaction, and allowed to stand and cool to room temperature to obtain a composite catalyst.

7. The main and fine gate integrated HJT silver paste according to claim 6, characterized in that: The imidazole is benzimidazole, DBU, dimethyltetraethylimidazole, PN23, PN23J, PN40, and the diacid is an organic diacid such as adipic acid, succinic acid, glutaric acid, and sebacic acid.

8. The main and fine gate integrated HJT silver paste according to claim 7, characterized in that: The silicone oil catalyst is Custer catalyst, tetramethylammonium chloride, Custer silicone oil type platinum catalyst.

9. The main and fine gate integrated HJT silver paste according to claim 8, characterized in that: The organic solvent is one or more of propylene carbonate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol butyl ether acetate, dimethyl adipate, diethyl adipate, propylene glycol methyl ether acetate, and terpineol.

10. A main-fine gate integrated HJT silver paste and a preparation method thereof, characterized in that: The steps include: 1) Add 2-5% organic solvent into a reaction kettle and mix, then add 2-5% resin, heat and stir, cool to room temperature, filter, and obtain a resin solution. The heating temperature is 70-95° C.; the stirring speed is 200-300 r / min, and the time is 1-2 hours; 2) adding 0.01-1% catalyst, 0.01-1% thixotropic agent, 0.5-2% curing agent and 1-2% diluent to the resin solution prepared in step 1), centrifugally dispersing to obtain an organic carrier at a centrifugal dispersion speed of 800-850 rpm for 2-4 minutes; 3) Add 87-93% of silver powder to the organic carrier prepared in step 2), centrifugally disperse, and then disperse by shearing with a three-roll mill until the slurry fineness is less than 5 μm, and filter to obtain a finished silver paste. The specific process of centrifugal dispersion is: disperse at 800 rpm, 1000 rpm, 1200 rpm, and 1600 rpm for 1 to 3 minutes each.

Citation Information

Patent Citations

  • High adhesion low temperature curing conductive paste and preparation method thereof

    CN109585090A

  • HJT photovoltaic silver paste and preparation method thereof

    CN114023487A

  • Low-resistivity low-temperature solar silver paste and preparation method thereof

    CN114464342A

  • Low-temperature silver paste for HJT solar cell

    CN116665948A

  • Conductive polymer dispersion liquid, conductive polymer-containing liquid, conductive laminate, capacitor, and method for producing same

    CN118173384A

Cited By

  • HJT silver paste and preparation method therefor

    WO2026118568A1